소비자·생산자·유통업계의 식품안전관련 의식 및 요구사항 조사 - 박재홍 (한국농촌경제연구원, 2004)
Under free trade circumstance, consumers' concerns to food safety are highly raised. To satisfy consumers needs for safe agricultural products, improving food safety in domestic agricultural products market is essential for farmers and distributors. The main objective of this study is to analyze current awareness and needs of consumers, producers and distributors regarding food safety, and propose some policy measures for improving food safety in connection with good agricultural practices. For this study, survey for 400 consumers in megalopolises, 37 various distributors in metropolitan area, 91 farmers in four provinces are conducted respectively. As first considered production and purchasing criteria, quality(taste) and price are considered. However, when only food safety and quality(taste) are compared, consumers are concerned relatively more about food safety. The grade for domestic agricultural products measured by consumers, producers and distributors is mostly 80-89. It implies domestic products are more trusted. The information on food safety comes from mass media for producers and consumers, same industry profession for distributors. Every survey indicates that the most important role for food safety is on producers. Many respondents are willing to pay more for production, distribution, consumption of safe agricultural products. Relatively less consumers are willing to pay more. It may be caused from uneasy feeling from additional expenditure with regular income. In addition, awareness for certifications is generally low, but high for distributors. Many respondents, especially consumers, do not know about good agricultural practices. As mentioned before about importance of producers for food safety, demand for training and consulting on farmers is high to good agricultural practices. It means that the importance of security of food safety at production stage is remarkably recognized. For labelling, most think that the result of pesticide and heavy metal residues inspection has to be labeled. Distributors will deal more food safety certified agricultural products in future. Also consumers are highly concerned with food safety. At present, most do not know good agricultural practices, but they agree the necessity of good agricultural practices and are willing to pay more. Thus, producers, distributors and government have to assure food safety and easy information exchange. Some policy alternatives for food safety and good agricultural practices are suggested as follows: Manual for high quality and safe agricultural products are necessary, Introduction of good agricultural practices that will improve current quality certification is requisite to, Above all things, active education and consulting to producers is essential, A far-reaching public information work, Training manpower in connection with good agricultural practices, Constructing infrastructure related to good agricultural practices, Continuous improvement of good agricultural practices.